It Looks Like a Zebra but Is Not: [18F]FDG PET/CT in a Giant Cutaneous Malignant Melanoma Mimicking Squamous Cell Carcinoma - Ilaria Proietti; Giulia Azzella; Diana Dirzu; Claudio Di Cristofano; Oreste Bagni; Concetta Potenza; Luca Filippi (Diagnostics)
Cutaneous malignant melanoma (MM) is the most aggressive form of skin cancer, associated with high mortality and rising incidence rates in Europe despite prevention efforts. Nodular MM, the most aggressive subtype, often mimics other skin tumors, complicating diagnosis. We present the case of a 66-year-old woman with a large, ulcerated tumor beneath the left scapula, along with multiple nodular lesions on the left arm and chest. Initially suspected to be an aggressive squamous cell carcinoma, the diagnosis was confirmed as invasive cutaneous MM with a BRAF(V600) mutation via biopsy. Staging with PET/CT revealed extensive glucose metabolism in the tumors and surrounding tissues, as well as metastatic lymphadenopathy. The disease was classified as stage IV (T4bN3cM1a0). Neoadjuvant systemic therapy with BRAF and MEK inhibitors (Dabrafenib and Trametinib) was initiated to reduce tumor size. Remarkable regression was observed within a week, with further reduction in tumor size after one month. A follow-up PET/CT after 3 months showed significant decreases in tracer uptake and lesion size, with a ΔSUVmax of 51.9%, a ΔMTV of 74.5%, and a ΔTLG of 83.5%, indicating an excellent response to targeted therapy.